Para além da academia: a atuação do cientista social no mercado privado de pesquisas - Marson, Fabricio de Oliveira (2023)
This research seeks to understand to what extent the training of Social Scientists contributes to their performance in the private research market and discusses the curricular notes of the Social Sciences courses of four Higher Education Institutions located in the city of São Paulo, which are: Pontifícia Universidade Católica de São Paulo (PUCSP), Fundação Escola de Sociologia e Política de São Paulo (FESPSP), Universidade de São Paulo (USP) and Escola Superior de Propaganda e Marketing (ESPM). It is not news that Social Scientists have always been present in research institutes in the private sector, however, it is necessary to understand what potentialities direct these professionals to this type of activity. This research involved eleven in-depth interviews with graduates, undergraduates and professors of Social Sciences courses at selected Higher Education Institutions and, in addition to seeking to understand the potential of Social Scientists in the face of the private research market, analyzing their conflicts of workers of these professionals in this type of activity